Design, synthesis and biological evaluation of erlotinib-based IDO1 inhibitors - Xi-xi Hou; Xiao-qing Gong; Long-fei Mao; Ge Sun; Ge Sun; Jian-xue Yang; Jian-xue Yang (Frontiers Media S.A., 2022)
Erlotinib is a highly specific and reversible epidermal growth factor receptor tyrosine kinase inhibitor for the targeted therapy of non-small-cell lung cancer (NSCLC) However, the efficacy of erlotinib is limited because the development of drug resistance during chemotherapy. Indoleamine 2,3-dioxygenase-1 (IDO1) is a rate-limiting tryptophan catabolic enzyme that is activated in many human cancers. In this study, we designed a series of erlotinib-based 1,2,3-triazole compounds by combining erlotinib with phenyl or benzyl azide. Attentive FP prediction model was used to predict the bioactivity of those compounds. We discovered that most of the erlotinib-based 1,2,3-triazole compounds are capable of suppressing IDO1 activities in vitro experiments. Among them, compound 14b (IC50 = 0.59 ± 0.05 μM) had the strongest inhibitory effect on IDO1. In addition, compound 14b significantly inhibited tumor growth comparable to the antitumor activity of erlotinib and the IDO1 inhibitor epacadostat in murine tumor models.